Los cuatro jinetes del Apocalipsis - Blasco Ibáñez, Vicente, 1867-1928 (Akal bolsillo, 2012)
Partly set in Argentina, partly in France this anti-German story describes the horrors of WW I as the background for a tragic story of illicit love.